Phenotypic diversity and glucocorticoid sensitivity in patients with familial partial lipodystrophy type 2. (15th April 2019) - Resende, Ana Teresa Prata; Martins, Clarissa Silva; Bueno, Ana Carolina; Moreira, Ayrton Custódio; Foss‐Freitas, Maria Cristina; de Castro, Margaret
Abstract: Summary: Familial partial lipodystrophy type 2 (FPLD2) is characterized by insulin resistance, adipose atrophy of the extremities and central obesity. Due to the resemblance with Cushing's syndrome, we hypothesized a putative role of glucocorticoid in the pathogenesis of metabolic abnormalities in FPLD2. Objective: To evaluate the phenotypic heterogeneity and glucocorticoid sensitivity in FPLD2 patients exhibiting the p.R482W or p.R644C LMNA mutations. Design, patients and measurements: Prospective study with FPLD2 patients (n = 24) and controls (n = 24), who underwent anthropometric, body composition, metabolic profile and adipokines/cytokine plasma measurements. Plasma and salivary cortisol were measured in basal conditions and after 0.25, 0.5 and 1.0 mg of dexamethasone (DEX) given at 23:00 hours. Glucocorticoid receptor ( GR) and 11βHSD isoforms expression were assessed by qPCR. Results: Familial partial lipodystrophy type 2 individuals presented increased waist and neck circumferences, decreased hip circumference, peripheral skinfold thickness and fat mass. Patients presented increased HOMA‐IR, triglycerides, TNF‐α, IL‐1β, IL‐6 and IL‐10, and decreased adiponectin and leptin plasma levels. FPLD2 patients showed decreased ability to suppress the HPA axis compared with controls after 0.5 mg DEX. The phenotype was more pronounced in patients harbouring the p.R482W LMNA mutation. GRβ overexpression in PBMC was observed in female patients compared with female controls. Conclusions: Familial partial lipodystrophy type 2 patients exhibited anthropometric, clinical and biochemical phenotypic heterogeneity related to LMNA mutation sites and to gender. LMNA mutations affecting both lamin A and lamin C lead to more severe phenotype. FPLD2 patients also showed blunted HPA axis response to DEX, probably due to the association of increased levels of proinflammatory cytokines with GRβ overexpression leading to a more severe phenotype in female.